5.3.26 Problems 2501 to 2600

Table 5.335: Second order ode

#

ODE

Mathematica

Maple

9522

\[ {}x^{2} y^{\prime \prime }+x y^{\prime }+\frac {\left (x^{2}-1\right ) y}{4} = 0 \]

9523

\[ {}x y^{\prime \prime }+\left (1-2 x \right ) y^{\prime }+\left (x -1\right ) y = 0 \]

9524

\[ {}x y^{\prime \prime }-\left (1+x \right ) y^{\prime }+y = 0 \]

9525

\[ {}x y^{\prime \prime }+3 y^{\prime }+4 x^{3} y = 0 \]

9526

\[ {}x^{2} \left (-x^{2}+1\right ) y^{\prime \prime }+2 x \left (-x^{2}+1\right ) y^{\prime }-2 y = 0 \]

9527

\[ {}2 x y^{\prime \prime }+\left (x -2\right ) y^{\prime }-y = 0 \]

9528

\[ {}x y^{\prime \prime }+2 y^{\prime }+x y = 0 \]

9529

\[ {}y^{\prime \prime }+2 x^{2} y^{\prime }+\left (x^{4}+2 x -1\right ) y = 0 \]

9530

\[ {}u^{\prime \prime }+\frac {u}{x^{2}} = 0 \]

9531

\[ {}u^{\prime \prime }-\left (2 x +1\right ) u^{\prime }+\left (x^{2}+x -1\right ) u = 0 \]

9532

\[ {}y^{\prime \prime }+2 y^{\prime }+\left (1+\frac {2}{\left (1+3 x \right )^{2}}\right ) y = 0 \]

9533

\[ {}x^{2} y^{\prime \prime }-2 x y^{\prime }+\left (x^{2}+2\right ) y = 0 \]

9534

\[ {}y^{\prime \prime }+\frac {2 y^{\prime }}{x}-\frac {2 y}{\left (1+x \right )^{2}} = 0 \]

9535

\[ {}y^{\prime \prime }+\frac {y}{2 x^{4}} = 0 \]

9536

\[ {}y^{\prime \prime }-x y^{\prime }-x y = 0 \]

9537

\[ {}y^{\prime \prime }-x y^{\prime }-x y = 0 \]

9538

\[ {}y^{\prime \prime }-x y^{\prime }-x y = 0 \]

9539

\[ {}y^{\prime \prime }-x y^{\prime }-x y = 0 \]

9540

\[ {}y^{\prime \prime }-x y^{\prime }-x y = 0 \]

9541

\[ {}y^{\prime \prime }-x y^{\prime }-x y = 0 \]

9542

\[ {}y^{\prime \prime }-x y^{\prime }-x y = 0 \]

9543

\[ {}y^{\prime \prime }-x y^{\prime }-x y = 0 \]

9544

\[ {}y^{\prime \prime }-x y^{\prime }-x y = 0 \]

9545

\[ {}y^{\prime \prime }-x y^{\prime }-x y = 0 \]

9546

\[ {}y^{\prime \prime }-x y^{\prime }-x y = 0 \]

9547

\[ {}x y^{\prime \prime }+2 y^{\prime }+x y = 0 \]

9548

\[ {}2 x^{2} y^{\prime \prime }+3 x y^{\prime }-x y = 0 \]

9549

\[ {}x^{2} y^{\prime \prime }+\left (3 x^{2}+2 x \right ) y^{\prime }-2 y = 0 \]

9550

\[ {}2 x^{2} \left (x^{2}+x +1\right ) y^{\prime \prime }+x \left (11 x^{2}+11 x +9\right ) y^{\prime }+\left (7 x^{2}+10 x +6\right ) y = 0 \]

9551

\[ {}x y^{\prime \prime }+\left (1+x \right ) y^{\prime }+2 y = 0 \]

9552

\[ {}x^{2} \left (x^{2}-2 x +1\right ) y^{\prime \prime }-x \left (x +3\right ) y^{\prime }+\left (x +4\right ) y = 0 \]

9553

\[ {}2 x^{2} \left (x +2\right ) y^{\prime \prime }+5 x^{2} y^{\prime }+\left (1+x \right ) y = 0 \]

9554

\[ {}x^{2} y^{\prime \prime }+4 x y^{\prime }+\left (x^{2}+2\right ) y = 0 \]

9555

\[ {}x^{2} y^{\prime \prime }+x y^{\prime }+\left (x^{2}-\frac {1}{4}\right ) y = 0 \]

9556

\[ {}x^{2} y^{\prime \prime }-x y^{\prime }-\left (x^{2}+\frac {5}{4}\right ) y = 0 \]

9557

\[ {}x^{2} y^{\prime \prime }+x y^{\prime }+\left (x^{2}-\frac {1}{4}\right ) y = 0 \]

9558

\[ {}x^{2} y^{\prime \prime }+3 x y^{\prime }+4 x^{4} y = 0 \]

9559

\[ {}y^{\prime \prime } = \left (x^{2}+3\right ) y \]

9560

\[ {}y^{\prime \prime }+2 x y^{\prime }+\left (x^{2}+1\right ) y = 0 \]

9561

\[ {}x^{3} y^{\prime \prime }+y^{\prime }-\frac {y}{x} = 0 \]

9562

\[ {}x^{2} y^{\prime \prime }+x y^{\prime }+\left (x^{2}-\frac {1}{4}\right ) y = 0 \]

9563

\[ {}4 x^{2} y^{\prime \prime }+\left (-8 x^{2}+4 x \right ) y^{\prime }+\left (4 x^{2}-4 x -1\right ) y = 0 \]

9564

\[ {}y^{\prime \prime }-y^{\prime }+y = 0 \]

9565

\[ {}\left (x^{2}-1\right ) y^{\prime \prime }-2 x y^{\prime }+2 y = 0 \]

9566

\[ {}x^{2} y^{\prime \prime }-x \left (x +2\right ) y^{\prime }+\left (x +2\right ) y = 0 \]

9567

\[ {}\left (1+x \right ) y^{\prime \prime }-\left (x +2\right ) y^{\prime }+y = 0 \]

9568

\[ {}\left (-x^{2}+1\right ) y^{\prime \prime }+2 x y^{\prime }-2 y = 0 \]

9569

\[ {}\left (-x^{2}+1\right ) y^{\prime \prime }-2 x y^{\prime }+2 y = 0 \]

9570

\[ {}x^{2} y^{\prime \prime }+x y^{\prime }+\left (x^{2}-\frac {1}{4}\right ) y = 0 \]

9571

\[ {}\left (x^{2}-1\right ) y^{\prime \prime }-6 x y^{\prime }+12 y = 0 \]

9572

\[ {}\left (x^{2}+3\right ) y^{\prime \prime }-7 x y^{\prime }+16 y = 0 \]

9573

\[ {}\left (x^{2}-1\right ) y^{\prime \prime }+8 x y^{\prime }+12 y = 0 \]

9574

\[ {}3 y^{\prime \prime }+x y^{\prime }-4 y = 0 \]

9575

\[ {}5 y^{\prime \prime }-2 x y^{\prime }+10 y = 0 \]

9576

\[ {}y^{\prime \prime }-x^{2} y^{\prime }-3 x y = 0 \]

9577

\[ {}\left (x^{2}+1\right ) y^{\prime \prime }+2 x y^{\prime }-2 y = 0 \]

9578

\[ {}y^{\prime \prime }+x y^{\prime }-2 y = 0 \]

9579

\[ {}\left (x^{2}-6 x +10\right ) y^{\prime \prime }-4 \left (x -3\right ) y^{\prime }+6 y = 0 \]

9580

\[ {}\left (x^{2}+6 x \right ) y^{\prime \prime }+\left (3 x +9\right ) y^{\prime }-3 y = 0 \]

9581

\[ {}t y^{\prime \prime }+\left (t^{2}-1\right ) y^{\prime }+t^{3} y = 0 \]

9582

\[ {}t^{2} y^{\prime \prime }-t \left (2+t \right ) y^{\prime }+\left (2+t \right ) y = 0 \]

9583

\[ {}\left (x -1\right ) y^{\prime \prime }-x y^{\prime }+y = 0 \]

9584

\[ {}x^{2} y^{\prime \prime }-\left (x -\frac {3}{16}\right ) y = 0 \]

9585

\[ {}x^{2} y^{\prime \prime }+x y^{\prime }+\left (x^{2}-\frac {1}{4}\right ) y = 0 \]

9586

\[ {}t^{2} y^{\prime \prime }-t \left (2+t \right ) y^{\prime }+\left (2+t \right ) y = 0 \]

9587

\[ {}t y^{\prime \prime }-\left (t +1\right ) y^{\prime }+y = 0 \]

9588

\[ {}\left (1-t \right ) y^{\prime \prime }+t y^{\prime }-y = 0 \]

9589

\[ {}x^{2} y^{\prime \prime }+x y^{\prime }+\left (x^{2}-\frac {1}{4}\right ) y = 0 \]

9590

\[ {}t y^{\prime \prime }-\left (t +1\right ) y^{\prime }+y = 0 \]

9591

\[ {}\left (1-t \right ) y^{\prime \prime }+t y^{\prime }-y = 0 \]

9592

\[ {}y^{\prime \prime }+x y^{\prime }+2 y = 0 \]

9593

\[ {}\left (x^{2}+1\right ) y^{\prime \prime }-4 x y^{\prime }+6 y = 0 \]

9594

\[ {}\left (1-x \right ) y^{\prime \prime }+x y^{\prime }-y = 0 \]

9595

\[ {}2 y^{\prime \prime }+x y^{\prime }+3 y = 0 \]

9596

\[ {}y^{\prime \prime }+x y^{\prime }+2 y = 0 \]

9597

\[ {}\left (1-x \right ) y^{\prime \prime }+x y^{\prime }-y = 0 \]

9598

\[ {}y^{\prime \prime }+x y^{\prime }+2 y = 0 \]

9599

\[ {}\left (-x^{2}+4\right ) y^{\prime \prime }+x y^{\prime }+2 y = 0 \]

9600

\[ {}4 x^{2} y^{\prime \prime }-4 x y^{\prime }+\left (-16 x^{2}+3\right ) y = 0 \]

9601

\[ {}\left (x -1\right ) y^{\prime \prime }-x y^{\prime }+y = 0 \]

9602

\[ {}x^{2} y^{\prime \prime }-2 x y^{\prime }+\left (x^{2}+2\right ) y = 0 \]

9603

\[ {}\left (x^{2}-2 x \right ) y^{\prime \prime }+\left (-x^{2}+2\right ) y^{\prime }+\left (2 x -2\right ) y = 0 \]

9604

\[ {}\left (2 x +1\right ) y^{\prime \prime }-2 y^{\prime }-\left (2 x +3\right ) y = 0 \]

9605

\[ {}4 x^{2} y^{\prime \prime }+\left (-8 x^{2}+4 x \right ) y^{\prime }+\left (4 x^{2}-4 x -1\right ) y = 0 \]

9606

\[ {}y^{\prime \prime }+4 x y^{\prime }+\left (4 x^{2}+2\right ) y = 0 \]

9607

\[ {}x^{2} y^{\prime \prime }+2 x \left (x -1\right ) y^{\prime }+\left (x^{2}-2 x +2\right ) y = 0 \]

9608

\[ {}x^{2} y^{\prime \prime }-x \left (2 x -1\right ) y^{\prime }+\left (x^{2}-x -1\right ) y = 0 \]

9609

\[ {}\left (1-2 x \right ) y^{\prime \prime }+2 y^{\prime }+\left (2 x -3\right ) y = 0 \]

9610

\[ {}2 x y^{\prime \prime }+\left (4 x +1\right ) y^{\prime }+\left (2 x +1\right ) y = 0 \]

9611

\[ {}x y^{\prime \prime }-\left (2 x +1\right ) y^{\prime }+\left (1+x \right ) y = 0 \]

9612

\[ {}4 x^{2} y^{\prime \prime }-4 x \left (1+x \right ) y^{\prime }+\left (2 x +3\right ) y = 0 \]

9613

\[ {}x y^{\prime \prime }+\left (-2 x +2\right ) y^{\prime }+\left (x -2\right ) y = 0 \]

9614

\[ {}x^{2} y^{\prime \prime }-2 x y^{\prime }+2 y = 0 \]

9615

\[ {}x y^{\prime \prime }-\left (2+2 x \right ) y^{\prime }+\left (x +2\right ) y = 0 \]

9616

\[ {}x^{2} y^{\prime \prime }-2 x y^{\prime }+\left (x^{2}+2\right ) y = 0 \]

9617

\[ {}x y^{\prime \prime }-\left (4 x +1\right ) y^{\prime }+\left (2+4 x \right ) y = 0 \]

9618

\[ {}4 x^{2} y^{\prime \prime }-4 x y^{\prime }+\left (-16 x^{2}+3\right ) y = 0 \]

9619

\[ {}\left (2 x +1\right ) x y^{\prime \prime }-2 \left (2 x^{2}-1\right ) y^{\prime }-4 \left (1+x \right ) y = 0 \]

9620

\[ {}\left (x^{2}-2 x \right ) y^{\prime \prime }+\left (-x^{2}+2\right ) y^{\prime }+\left (2 x -2\right ) y = 0 \]

9621

\[ {}x y^{\prime \prime }-\left (4 x +1\right ) y^{\prime }+\left (2+4 x \right ) y = 0 \]